ChemInform Abstract: A 14‐Membered Macrolide and Isocoumarin Derivatives from the Cultured Lichen Mycobionts of Graphis vestitoides. Issue 33 (25th July 2013) - Le, Duy; Hoang, Hoang; Takenaka, Yukiko; Hamada, Nobuo; Miyawaki, Hiromi; Tanahashi, Takao
Abstract Isocoumarin (I) and the 14‐membered macrolide ((S)‐II) are isolated along with five known isocoumarin derivatives.